Significantly lower infection fatality rates associated with SARS-CoV-2 Omicron (B.1.1.529) infection in children and young people: Active, prospective national surveillance, January-March 2022, England. Issue 4 (April 2023) - Hani, Erjola; Bertran, Marta; Powell, Annabel; Williams, Hannah; Birrell, Paul; DeAngelis, Daniela; Ramsay, Mary E; Oligbu, Godwin; Ladhani, Shamez N
Highlights: Children and young people (CYP) have a low risk of severe or fatal COVID-19. The Omicron wave since late 2021 was associated with very low infection rates in CYP. The infection fatality rate following Omicron infection was 2 per million infections. Infection fatality rate was 7-fold lower with Omicron than the first pandemic wave. Most deaths occurred in CYP with severe comorbidities, especially neurodisabilities.